Papers - Mineral Industry Education - Applied Psychology in the Payment of Bonuses, Whether for Increased Service or Mine Safety (Abstract) - Eugene McAuliffe (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1934)
The management of The Union Pacific Coal Co., which operates a group of coal mines in Southern Wyoming, believes in the value of applied psychology as a productive factor in the work of getting out coal. Operating almost wholly through the medium of mechanical loading machinery, the company has for some years paid a bonus, equivalent to one-half the labor saving made above a determined average output per shift worked, on a given machine. No penalty is attached where the established output is not obtained, but in 1933 the men on one class of machines earned an average premium of $0.633 per shift on 56.4 per cent of the tonnage loaded. On another class of machine, the men earned an average premium of $0.686 per shift on 28.4 per cent of the tonnage loaded An increase of 36 per cent in tons loaded per man-shift has resulted since the program was instituted. This coal company has also been very successful in reducing mine accidents through prizes awarded in an unusual way. At the close of the year, every man whose particular mine section passes through the year without a lost-time accident is given a ticket entitling him to participate in a safety drawing where an automobile is awarded as first prim.. There are also a number of cash safety prizes which are similarly awarded. Some 1500 persons attend the drawing, which excites much interest and attention. The particular plan employed, the payment of production bonus awards and safety prizes, is foundationed upon collective. rather than individual effort, and, once gotten under way, has proved to be substantlally self-cnforcing.